THE EFFECT OF BARIUM SUBSTITUTION WITH COMBINATIONS OF RARE EARTH ON PERMANENT MAGNETIC SURFACE MORPHOLOGY BASED ON BARIUM HEXAFERRITE - Adnyana, I Gusti Agung Putra; Suarbawa, Komang Ngurah; Nurmalasari, Ni Putu Yuni; Adi, Wisnu Ari (Universitas Mataram, 2024)
The development of hard magnets today is progressing very rapidly. Developing hard magnets based on rare earth metals becomes a severe problem when the raw materials are not readily available. The chosen solution is to replace oxide-based permanent magnets with small amounts of rare earth metals substituted to improve their magnetic properties. This study synthesized a permanent magnet oxide based on barium hexaferrite doped with lanthanum and cerium atoms. In the synthesis of this material, a mechanical wet milling technique is used to obtain a single-phase permanent magnetic Ba1-Î²-Î³LaÎ²CeÎ³Fe12O19 system with composition (Î² = 0 - 0.5 and Î³ = 0 - 0.1). The precursors are weighted according to their stoichiometric composition. Each mixed composition was milled by high energy milling (PW 1000 in the mixer/mill) at a milling speed of 1000 rpm using steel balls with an average diameter of 12 mm. Grinding conditions included a ball-to-powder weight ratio of 2:1, milling time 5 hours, then compacted with 7000 Psi pressure and sintered at 1200oC for 2 hours. The surface morphology and microstructure of the resulting sample particles were observed using scanning electron microscopy (SEM) with the SEM JEOL JED 305 brand. The characterization results show that the particles are hexagonally homogeneous in shape with particle sizes in the range of 1000-2000 nm for Î² = 0 and Î³ = 0 (without doping). In general, the four samples with varying concentrations of doping ions La3+ and Ce4+ showed homogeneous hexagonal structures but smaller particle sizes than pure barium hexaferrite. The sample particle sizes ranged from 500-1000 nm for Î² = 0.02 and 300-1000 nm for Î² = 0.04.